A tutela jurídica do meio ambiente de trabalho frente aos riscos potenciais dos nanomateriais manufaturados - Petry, Mariana (My University, 2022)
In the Brazilian legal system, the healthy and balanced work environment is a fundamental right, in addition, the worker must be guaranteed social protection, ensuring that the exercise of work does not harm the fundamental rights to health and life. Based on this premise, the objective of this dissertation was to analyze and understand whether the Brazilian legal system is fulfilling the constitutional duties established in the protection of workers against unknown risks in the handling of engineered nanoparticles in the work environment. Currently, even after decades of development of nanotechnologies, gaps persist in scientific knowledge related to risks to the health and physical integrity of workers, resulting from exposure to manufactured nanomaterials in the work environment. In the Brazilian legal system for the protection of the working environment, both labor law and social security law protect only known risks and foreseen in rules and regulatory decrees. The labor law, when restricted to norms of a preventive nature, dependent on proof and regulation, does not respond effectively to the new risks of nanomaterials, prevents or hinders the application of the precautionary principle, in the constitutional protection of the right to a healthy quality of life. of the worker. The social security law, in spite of its preventive nature, has shown a tendency towards openness in relation to the exhaustiveness of the lists provided for in the regulatory decrees, admitting the exemplary nature of the lists. The Precautionary Principle, along with the prevention principle, can be used to develop more effective methods of managing these new risks, it just needs a broader understanding of these new risks and a deeper interpretation of existing rules and instruments. The methodology used for the present investigation was exploratory bibliographic research, legislation research and data in the specialized literature. The method adopted was the hypothetical-deductive, seeking to find out how the law should provide the appropriate response to the risks associated with nanotechnology in the work environment. [resumo fornecido pelo autor]
No ordenamento jurídico brasileiro, o meio ambiente de trabalho sadio e equilibrado trata-se de um direito fundamental, além disso, ao trabalhador deve ser garantida proteção social, assegurando que o exercício do trabalho não prejudique os direitos fundamentais à saúde e à vida. Partindo dessa premissa, o objetivo da presente dissertação foi analisar e compreender se o sistema jurídico brasileiro está cumprindo os deveres constitucionais de proteção do trabalhador frente aos riscos desconhecidos no manuseio de nanopartículas engenheiradas no meio ambiente laboral. Atualmente, mesmo após décadas de desenvolvimento das nanotecnologias, persistem lacunas no conhecimento científico relacionada aos riscos à saúde e à integridade física dos trabalhadores, decorrentes da exposição à nanomateriais manufaturados no ambiente de trabalho. No sistema jurídico brasileiro de proteção ao meio ambiente laboral, tanto o direito trabalhista, quanto o direito previdenciário, tutelam apenas os riscos conhecidos e previstos em normas e decretos regulamentares. O direito do trabalho ao restringir-se a normas de natureza preventiva, dependentes de comprovação e regulamentação não responde de maneira eficaz aos novos riscos dos nanomateriais, impede ou dificulta a aplicação do princípio da precaução, na proteção constitucional do direito à sadia qualidade de vida do trabalhador. Já o direito previdenciário, em que pese, também tenha natureza preventiva, vem mostrando uma tendência de abertura em relação a taxatividade das listas previstas nos decretos regulamentares, admitindo o caráter exemplificativo das listas. O Princípio da Precaução, ao lado do princípio da prevenção, pode ser utilizado para o desenvolvimento de métodos mais eficazes de gestão desses novos riscos necessitando apenas de uma compreensão mais ampla desses novos riscos e uma interpretação mais profunda das normas e instrumentos já existentes. A metodologia utilizada para a presente investigação foi pesquisa bibliográfica exploratória, pesquisa de legislação e de dados na literatura especializada. O método adotado foi o hipotético-dedutivo, buscando averiguar de que forma o direito deverá dar a resposta adequada para os riscos associados à nanotecnologia no meio ambiente laboral. [resumo fornecido pelo autor]
Keywords: Direito do trabalho; Meio ambiente; Segurança do trabalho; Materiais nanoestruturados; Precaução (Direito); Labor laws and legislation; Environment; Industrial safety; Nanostructured materials; Precautionary principle